Trends and Future Directions in Online Marketing Research. Issue 1 (2nd January 2017) - Roy, Gobinda; Datta, Biplab; Basu, Rituparna
ABSTRACT: Over the last decade, the increased adoption of the Internet in public life as well as in developing businesses has led to a phenomenal rise in academic research on online marketing. This article is set to extensively review scholarly articles appearing from 2000 to 2014 on the topic from 10 top-tier academic journals to understand the research trends in the domain. A literature review has reported eight major subjective categories with an analysis of online marketing effectiveness framework. This review found three most significant subject categories: (1) online marketing issues; (2) Internet usage, perception, and attitude; and (3) online shopping and e-commerce. Additionally, some new online marketing research topics such as word-of-mouth, user-generated content, and social network are also highlighted. Finally, a selection of research topics that got the maximum attention of researchers is presented along with discussion of the future research directions in the online marketing space.